Japanese Effective Exchange Rates and Determinants : Prices, Real Interest Rates, and Actual and Optimal Current Accounts - Nagayasu, Jun (IMF Working Papers; Working Paper, 1998)
This paper empirically analyzes Japanese long-run exchange rates from several perspectives. Several exchange rate models are considered, including the purchasing power parity, the real interest differential model, and the hybrid models a la Hooper and Morton (1982). A notable feature of the latter models is that the current accounts are introduced as determinants of the exchange rates; one type of hybrid model uses the actual current account, and the other the optimal current account, which is calculated using the present value model suggested by Campbell and Shiller (1988). The paper finds that the long-run specification is sensitive to the specification of the model.